Makna Bermegah Dalam Kristus dalam Surat Filipi dan Implikasinya Bagi Hamba Tuhan - Gadiman Baene; Mozes lawalata (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
One of the aims of this writer is to provide an explanation of the meaning of boasting in christ and its implications for god's people. talking about boasting what is meant here is to lead to things that are centered on christ. and not boast in outward things as the main thing. but the main priority paul refers to here is spiritual matters. paul has a uniqueness that cannot be explained here but can be described through a physical relationship that can be expressed in a decision paul makes in his life. paul realized that it was only a vanity and carnality. there are many things that paul said in letters he had written such as in rome it was said that there is no pride outside of christ (rom.5:1-11). pride in christ is not because of your own efforts but because of god's grace.